2016
DOI: 10.1177/2010105816653137
|View full text |Cite
|
Sign up to set email alerts
|

A cohort survey of the effect of an educational intervention on human papillomavirus vaccine-related knowledge and attitudes among pre-university female students in Singapore

Abstract: Introduction: Although cervical cancer is the 10th most common cancer among females in Singapore, it is a vaccinepreventable cancer. Human papillomavirus vaccines combined with regular Pap (papillomavirus) smears have been shown to reduce the mortality and morbidity associated with cervical cancer. We assessed the knowledge and attitudes towards cervical cancer, human papillomavirus and its vaccination amongst pre-university female students and assessed if a short educational presentation can improve this know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Post-intervention, all fifteen studies reported a statistically significant improvement in their specific outcome measures including changes in knowledge, attitude and perception with regard to HPV vaccination and associated cancer prevention. All of the studies aimed to improve knowledge related to HPV risk and HPV vaccination while many focused on improving positive attitudes/perceptions regarding self-protection against acquirement of HPV 3,8,22,28,37,38,51,52,57,58 . Only 3 of the fifteen studies explored the actual effect of the intervention on HPV vaccination uptake 3,8,51 .…”
Section: Outcome Measures Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Post-intervention, all fifteen studies reported a statistically significant improvement in their specific outcome measures including changes in knowledge, attitude and perception with regard to HPV vaccination and associated cancer prevention. All of the studies aimed to improve knowledge related to HPV risk and HPV vaccination while many focused on improving positive attitudes/perceptions regarding self-protection against acquirement of HPV 3,8,22,28,37,38,51,52,57,58 . Only 3 of the fifteen studies explored the actual effect of the intervention on HPV vaccination uptake 3,8,51 .…”
Section: Outcome Measures Of Studiesmentioning
confidence: 99%
“…Six additional studies recorded 'intention to be vaccinated' against HPV after the intervention 22,28,37,38,56,57 . Four of the fifteen studies 3,8,51,52 explored the impact of the intervention on sexual behavior intention including condom use.…”
Section: Outcome Measures Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations